Detection and Investigation of Eagle Effect Resistance to Vancomycin in Clostridium difficile With an ATP-Bioluminescence Assay - Jarrad, Angie M.; Blaskovich, Mark A. T.; Prasetyoputri, Anggia; Karoli, Tomislav; Hansford, Karl A.; Cooper, Matthew A. (Frontiers in Microbiology, 2018)
Vancomycin was bactericidal against Clostridium difficile at 8-fold the minimal inhibitory concentration (MIC) using a traditional minimum bactericidal concentration (MBC) assay. However, at higher concentrations up to 64  MIC, vancomycin displayed a paradoxical ‘more-drug-kills-less’ Eagle effect against C. difficile. To overcome challenges associated with performing the labor-intensive agar-based MBC method under anaerobic growth conditions, we investigated an alternative more convenient ATP-bioluminescence assay to assess the Eagle effect in C. difficile. The commercial BacTitre-GloTM assay is a homogenous method to determine bacterial viability based on quantification of bacterial ATP as a marker for metabolic activity. The ATP-bioluminescence assay was advantageous over the traditional MBC-type assay in detecting the Eagle effect because it reduced assay time and was simple to perform; measurement of viability could be performed in less than 10 minutes outside of the anaerobic chamber. Using this method, we found C. difficile survived clinically relevant, high concentrations of vancomycin (up to 2048 µg/mL). In contrast, C. difficile did not survive high concentrations of metronidazole or fidaxomicin. The Eagle effect was also detected for telavancin, but not for teicoplanin, dalbavancin, oritavancin or ramoplanin. All four pathogenic strains of C. difficile tested consistently displayed Eagle effect resistance to vancomycin, but not metronidazole or fidaxomicin. These results suggest that Eagle effect resistance to vancomycin in C. difficile could be more prevalent than previously appreciated, with potential clinical implications. The ATP-Bioluminescence assay can thus be used as an alternative to the agar-based MBC assay to characterise the Eagle effect against a variety of antibiotics, at a wide-range of concentrations, with much greater throughput. This may facilitate improved understanding of Eagle effect resistance and promote further research to understand potential clinical relevance.